Ari J. Blatt and Edward Welch, editors. France in Flux: Space, Territory, and Contemporary Culture. Liverpool UP, 2019. - Suzanne Black (Studies in 20th & 21st Century Literature, 2022)
Review of Ari J. Blatt and Edward Welch, editors. France in Flux: Space, Territory, and Contemporary Culture. Liverpool UP, 2019. xiii + 221 pp.
Keywords: flux; space; 21st century France; film; photography; television